Answer:
0.64285714285
Step-by-step explanation:
8 + 6 = 14
9/14 = 0.64285714285
0.64285714285 * 14 = 9
Please vote Brainliest (:
Step-by-step explanation:
x - 1 = - 3x - 14
Bringing like terms on one side
x + 3x = -14 + 1
4x = - 13
x = - 13/4
Answer:
In standard form it is x^4 - 12x^3y + 54x^2y^2 - 108x y^3 + 81y^4.
Step-by-step explanation:
(3y)^4 + 4C1(3y)^3(-x) + 4C2(3y)^2(-x)^2 + 4C3(3y)(-x)^3 + (-x)^4
= 81y^4 - 108y^3x + 54y^2x^2 - 12yx^3 + x^4
(0,0) and (6,0)
First we subtract 18x from both sides
3x²-18x=0
Factor out a 3x
3x(x-6)=0
This means that x is either 0 or 6